THE EFFECT OF USING COMPLETE SENTENCE MODEL ON STUDENTS’ WRITING PARAGRAPH (A STUDY AT THE NINTH GRADE OF SMP NEGERI 2 SIBABANGUN 2020-2021 ACADEMIC YEAR) - iman hartati waruwu (JURNAL LINER (Language Intelligence and Educational Research), 2020)
Abstract: The aim of this research are to know: 1) the application of complete sentence model on teaching writing paragraph ability, 2) the students writing paragraph ability before and after using complete sentence model, 3) Whether there is any significant effect of complete sentence model on teaching writing paragraph ability at the Ninth Grade Students of SMP Negeri 2 Sibabangun. This research uses experimental method with the pre-experimental design by using one-group pretest and posttest design. The population of this research was all of the IX grade students’ of SMP Negeri 2 Sibabangun which consist of 84 students. Sample were IX C which consist of 29 students which taken by purposive sampling. In collecting the data the researchers uses observation sheet and test as an instrument. The result of this research: 1) the application of complete sentence model was 3.4, it was categorized “Good”. 2) the mean score of the students’ writing paragraph ability was 39 and it was categorized “fail”. Meanwhile, after using complete sentence model was 75, it is categorized “good”. The result of data analysis shows that ttest was higher than ttable(ttest11.78>ttable2.05). So, the hypothesis was accepted. It means that, there is any significant effect of complete sentence on students’ writing paragraph ability at the IX grade students of SMP N 2 Sibabangun Keywords: Complete Sentence Model, Writing Paragraph Ability Abstrak:Tujuanpenelitianiniadalahuntukmengetahui: 1) Penggunaan Complete Sentence Model dalammengajarmenulis paragraph, 2) Kemampuanmenulisparagrafsiswasebelumdansesudahmenggunakancomplete sentence model, 3) Apakahadapengaruh yang signifikandaricomplete sentence model terhadapkemampuanmenulissiswa di kelas IX SMP Negeri 2 Sibabangun. Penelitianinimenggunakanmetodeeksperimentaldenganrancanganpenelitian pre-eksperimental: one group pre-test post-test design. Populasipenelitianterdiridari 84 siswadan sample terdiridari 29 siswadenganmenggunakanteknik purposive sampling. Dalampenggumpulan data, penelitimenggunakanlembarobservasiuntukmenjaring data daripengaplikasian complete sentence dantesuntukmenjaring data darikemampuanmenulissiswa. Hasilpenggunaan complete sentence model dalammengajarkemampuanmenulissiswaadalah 3.4, di kategorikan “Baik”. Nilai rata-rata kemampuanmenulissiswasebelummenggunakan complete sentence model adalah 39, dikategorikan “gagal”. Sementarasetelahmenggunakan complete sentence model adalah 75, dikategorikan “baik”. Penelitimenggunakan proses statistikdalamanalis data , yaiturumusttest.. Berdasarkandata yang telah di analisis, hasilanalisisdata menunjukanbahwattestlebihbesardaripadattable (ttest11.78>ttable2.05). Jadi, hipotesisditerima. Iniberartiadapengaruh yang signifikiandariIcomplete sentence model terhadapkemampuanmenulissiswa di kelas IX SMP Negeri 2 SibabangunpadaTahunAjaran 2020/2021. Kata kunci: Complete Sentence Model, KemampuanMenulisParagraf